Overview of Hygiene and Sanitation of Street Vendor Snacks at Campus IV UIN North Sumatra Medan Tuntungan 2023 - Meutia Nanda; Suci Wahyuni; Hikmathine Osella Putri; Anggina Bancin; Annisa ul Husna; Arifin Shaleh Lubis (PROMOTOR, 2024)
Hygiene is a health effort to maintain and protect the cleanliness of food, such as washing hands with clean water and soap to protect hand hygiene, washing dishes to keep plates clean, and throwing away damaged parts of food to protect the integrity of the food as a whole. Sanitation is an effort to prevent disease that focuses on emphasizing activities on human environmental health efforts. Sanitation is a health effort to maintain and protect the cleanliness of the environment of the subject. Cleanliness and clean sanitation will make the presentation of food provide added value and attract customers when it is distributed. Therefore, there are various technical methods for serving food to consumers as long as they pay attention to appropriateness or good hygiene and sanitation. According to BPOM, in 2017, 5,293 people were exposed to food poisoning, which was dominated by microbiology. Meanwhile, 2,041 cases of extraordinary events (KLB) have been reported and 3 people died. This research is a descriptive observational study with a quantitative approach. The variables used in this research are handler hygiene, equipment sanitation, serving sanitation, and vendor facility sanitation. In assessing hygiene and sanitation, this research is guided by the regulations of the Decree of the Minister of Health of the Republic of Indonesia No. 92/MENKES/SK/VII/2003 concerning guidelines for hygiene and sanitation requirements for snack foods. This research was conducted on street vendors at Campus IV UINSU Tuntungan. The total sample was 30 street vendors using a simple random side sampling technique. In collecting data using observation and interview techniques. The data sources used are primary data which comes from interviews and observations, while secondary data comes from previous research. Data analysis uses univariate analysis to produce the distribution and frequency of each variable, namely a description of hygiene and sanitation, hygiene of handlers, sanitation of equipment, sanitation of serving, and sanitation of vending facilities is presented in the form of tables and tables. Suggestions are expected to avoid contamination of food equipment, especially germs, it is necessary to improve equipment sanitation such as washing equipment using clean water and using soap and drying equipment using a dryer or clean cloth. Handlers should wash their hands before and after work. The government and POM should carry out routine supervision and inspections in school canteens, catering services, and street snacks, especially around campuses.